Academic Burnout and the Quality of Students’ Thesis Proposal Background (A Correlational Study) - Nugroho, M Hasan; Ribahan, Ribahan; Jannah, Miftahul; Jaelani, Jaelani (Institut Agama Islam Negeri (IAIN) Manado, 2025)
Academic burnout has become a growing concern in higher education, especially among students engaged in cognitively demanding tasks like thesis writing. This study examines the relationship between academic burnout and the quality of the “Background of the Study” section in undergraduate theses among English Education students at Universitas Islam Negeri Mataram. Using a quantitative correlational design, the research investigates whether burnout—measured in terms of exhaustion and disengagement—affects academic writing performance. A purposive sampling technique was used to select 31 final-year students who met specific inclusion criteria. The Oldenburg Burnout Inventory (OLBI) measured burnout levels, while a rubric-based assessment evaluated writing quality. Due to non-normal data distribution, Spearman’s Rank Correlation was used for analysis. Results revealed a statistically significant negative correlation between exhaustion and writing quality, indicating that higher levels of exhaustion are associated with poorer academic writing. However, disengagement showed no significant relationship with writing quality. These findings suggest that exhaustion plays a more critical role in diminishing students’ cognitive performance during thesis writing. The study contributes to the existing literature on academic burnout and provides practical insights for educators, academic advisors, and institutions. Understanding how exhaustion impairs writing can support the development of targeted interventions, particularly in stress management and academic writing support, within faith-based higher education settings.Keywords: academic burnout, exhaustion, disengagement, thesis writing, writing quality